2015
DOI: 10.1186/1471-227x-15-s2-s1
|View full text |Cite
|
Sign up to set email alerts
|

The Pakistan National Emergency Department Surveillance Study (Pak-NEDS): Introducing a pilot surveillance

Abstract: BackgroundEvidence-based decision making is essential for appropriate prioritization and service provision by healthcare systems. Despite higher demands, data needs for this practice are not met in many cases in low- and middle-income countries because of underdeveloped sources, among other reasons. Emergency departments (EDs) provide an important channel for such information because of their strategic position within healthcare systems. This paper describes the design and pilot test of a national ED based sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…A recently published study [ 5 ] reported 3335 fall-related injuries, and it was observed that a majority of the falls were due to slipping ( n = 671, 56.6%), followed by falls from heights ( n = 338, 28.5%). About two-thirds ( n = 675, 66.6%) of fall injuries involved extremities, followed by head/neck injuries ( n = 257, 25.4%) and facial injuries ( n = 99, 9.8%).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study [ 5 ] reported 3335 fall-related injuries, and it was observed that a majority of the falls were due to slipping ( n = 671, 56.6%), followed by falls from heights ( n = 338, 28.5%). About two-thirds ( n = 675, 66.6%) of fall injuries involved extremities, followed by head/neck injuries ( n = 257, 25.4%) and facial injuries ( n = 99, 9.8%).…”
Section: Introductionmentioning
confidence: 99%
“…As not all LMICs can currently support such actions, collaboration either regionally or globally with institutions able to support education and mentoring of LMICs researches will be beneficial. An example of a successful longitudinal initiative exists in Pakistan, where a collaborative research and training programme with institutional buy-in for injury prevention and treatment work has been developed and produces not only high-quality emergency care research but also an enhanced pool of local researchers and scientific outputs 22 23…”
Section: Emergency Care Research In Lmics: Challenges and Strategiesmentioning
confidence: 99%
“…[35][36][37] Karachi has a number of public and private tertiary care teaching hospitals with EDs caring for hundreds of patients every day. 16 WTR is an acute issue for ED-based HCWs. A shortage of HCWs in EDs has not only adversely affected public health emergencies such as COVID-19 recently, but also has significantly impacted care delivery in mass casualty incidents and weather emergencies.…”
Section: Project Settingmentioning
confidence: 99%
“…[13][14][15] The ED is the gateway of the health care system in many LMICs such as Pakistan. 16 It is a common assumption that during a disaster, health care facilities would have adequate and appropriate staff and resources to care for the injured, acutely ill, and their families and would also provide appropriate care to others. In real life, whether an ED HCW would report to or remain at work when a disaster occured depends upon their personal preparedness, dependent care, and concerns for personal and family safety.…”
mentioning
confidence: 99%